2010
DOI: 10.1186/1471-2180-10-122
|View full text |Cite
|
Sign up to set email alerts
|

The dissemination of C10 cysteine protease genes in Bacteroides fragilis by mobile genetic elements

Abstract: BackgroundThe C10 family of cysteine proteases includes enzymes that contribute to the virulence of bacterial pathogens, such as SpeB in Streptococcus pyogenes. The presence of homologues of cysteine protease genes in human commensal organisms has not been examined. Bacteroides fragilis is a member of the dominant Bacteroidetes phylum of the human intestinal microbiota, and is a significant opportunistic pathogen.ResultsFour homologues of the streptococcal virulence factor SpeB were identified in the B. fragil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 62 publications
2
13
0
Order By: Relevance
“…We have previously demonstrated the transcriptional coupling of B. fragilis C10 protease genes with those for staphostatin-like inhibitors [9]. In the current study transcriptional coupling was also identified for the B. thetaiotaomicron btp and bti genes by Reverse Transcriptase PCR.…”
Section: Discussionsupporting
confidence: 63%
“…We have previously demonstrated the transcriptional coupling of B. fragilis C10 protease genes with those for staphostatin-like inhibitors [9]. In the current study transcriptional coupling was also identified for the B. thetaiotaomicron btp and bti genes by Reverse Transcriptase PCR.…”
Section: Discussionsupporting
confidence: 63%
“…This difference in the distribution of bft gene may be related to the severity of illness, prior antimicrobial therapy, type of the diet and thus gut flora and the method used to detect the enterotoxin. In addition, more than half (51.2%) of the isolates from bloodstream infections in Kuwait were enterotoxin producers which was much higher than previous reports from the USA and Japan (19)(20)(21)(22)(23)(24)(25)(26)(27)(28) et al, 1996, respectively) [16,28]. In our study, simultaneous harboring of 2, 3 and 4 bfp isotypes occurred in 71, 33 and 6 isolates, respectively, which is higher than those reported by Sarvari et al, and among the most bft-positive strains, bfp-1 was the most prevalent isotype.…”
Section: Discussionmentioning
confidence: 63%
“…This equates with 16.2% of the 210 bft-positive isolates. The sources of these resistant isolates were WIs [23], biopsy samples [4], BSI [3] and LRTIs [3]. A cfiA gene was detected in one B. fragilis strain that showed susceptibility to both imipenem and meropenem with MIC of 2 and 4 μg/ml, respectively.…”
Section: Bacterial Isolatesmentioning
confidence: 99%
“…Homologs of these genes were detected in both clinical isolates of B. fragilis and normal human fecal microbiota. 94 Another example is tetQ, a gene located on conjugative transposons of the Bacteroides species in the gut, but on an insertion sequence 21 (IS21) family transposon in the Prevotella species in the oral cavity. 95 This observation not only indicates HGT, but also different routes of dissemination of the same resistance gene by HGT in two locations of the GIT.…”
Section: Progress In the Study Of Antibiotic Resistance And Its Spreamentioning
confidence: 99%